Proteomic study of Akkermansia muciniphila and Bifidobacterium species co-culture under different carbon sources - Sulaiman, Jordy Evan; Zhan, Yuewei; Wang, Shuchen; Lai, Ka Lun; Li, James Ho Wa; Yutong, Daniel Ye; Tsim, Karl Wah Keung; Cheng, Kenneth King Yip; Lai, Yong; Lam, Henry (Frontiers in Microbiology, 2025)
Akkermansia muciniphila and Bifidobacterium spp. are major probiotic strains that have been shown to improve host metabolism and treat metabolic diseases. Previous studies have proposed formulating these probiotics as a therapeutic product to improve efficacy, but how they affect the growth and protein expression of each other in response to different nutrient environments remains unexplored. Here, we performed label-free quantitative proteomics on A. muciniphila and two Bifidobacterium species, Bifidobacterium longum and Bifidobacterium breve, in the presence of different carbon sources. Akkermansia muciniphila displayed distinct growth profiles when co-cultured with B. breve and B. longum in media containing monosaccharides (glucose and N-acetyl-D-glucosamine) or mucin. Akkermansia muciniphila led to reduced abundance of B. longum in co-culture compared to monoculture, irrespective of whether the media contained monosaccharides or mucin. By contrast, B. breve led to reduced abundance of A. muciniphila in co-culture compared to monoculture in the presence of the monosaccharides but not in the mucin medium. Proteomics analysis revealed that B. breve induced substantial alterations in the protein expression of A. muciniphila when cultured in the media with monosaccharides, but the two species minimally affected each other’s protein expression when cultured in the mucin medium. By screening health-relevant dietary fibers, we discovered that arabinoxylan selectively boosts the growth of B. longum in monoculture and co-culture. Notably, in the presence of arabinoxylan, B. longum promotes the growth of A. muciniphila and increases the expression of Amuc_1100 protein, leading to the enhancement of barrier integrity of intestinal epithelial cells. In sum, we demonstrated that glycans shape the growth and proteome profiles of A. muciniphila and B. breve or B. longum co-cultures and highlight that dietary fibers can be utilized to improve the functionality of the probiotic community.